2019
DOI: 10.9734/jabb/2019/v21i330095
|View full text |Cite
|
Sign up to set email alerts
|

Sero-prevalence and Risk Factors for Hepatitis A Virus Infection among Pregnant Women at the Samandin Medical Center, Ouagadougou, Burkina Faso

Abstract: Aims: This study determined prevalence and possible risk factors associated with HAV infection and compared Immunochromatography (IgG) rapid point of care test with standard ELISA test for diagnosis. Study Design:  Cross sectional epidemiological survey. Place and duration of Study: The study was carried out at the Samandin Medical Center (Ouagadougou, Burkina Faso), from July 2017 to December 2017. Methodology: A total of 180 pregnant women were recruited at the Samandin Medical Center. Anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
0
0
Order By: Relevance
“…False-negative and positive results were evaluated in the ICT test, as the current study indicated that the percentage of false-negative results in the ICT test was large (3.4%). This could be attributed to a decrease in sensitivity caused by the difficulty of detecting antibodies with low concentrations and poor affinity; compared to ELISA, the current study results agreed with other studies in the world 10,[13][14][15] .…”
Section: Resultssupporting
confidence: 89%
“…False-negative and positive results were evaluated in the ICT test, as the current study indicated that the percentage of false-negative results in the ICT test was large (3.4%). This could be attributed to a decrease in sensitivity caused by the difficulty of detecting antibodies with low concentrations and poor affinity; compared to ELISA, the current study results agreed with other studies in the world 10,[13][14][15] .…”
Section: Resultssupporting
confidence: 89%
“…An LFT that detects IgM anti-HAV from serum or plasma samples in 20 min was reported to have 100% sensitivity and 99% specificity when compared with an enzyme immunoassay for testing 150 samples from patients with acute HAV infections and 75 healthy individuals [65]. The Bioline HAV IgG/IgM Rapid Test (Abbott Diagnostics, Abbott Park, IL, USA), which allows for multiplex detection of both IgG and IgM anti-HAV from serum or plasma in 20 min, was evaluated against laboratory immunoassays using patient cohorts from Brazil, Burkina Faso, and India [66][67][68]. These reports suggest different performance characteristics for the detection of the two antibody isotypes.…”
Section: Hepatitis a Virusmentioning
confidence: 99%